Beethoven and the Creative Process - Cooper, Barry (Oxford Clarendon, 1990)
Beethoven's habit of composing by making large numbers of preliminary drafts and sketches was sufficiently unusual to attract attention even during his lifetime, and his creative process has attracted a good deal more attention since. The present book incorporates the findings of recent studies on this fascinating subject as well as providing many additional new insights. Cooper examines Beethoven's underlying creative motivation and there is and introduction to his compositional methods in general. The final part of the book is a detailed study of particular compositional problems in six different works, selected to provide a wide range of genres, dates, and types of problem. The book as a whole adds considerably to our understanding of one of the greatest figures in the history of our culture.
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Composing